PENGARUH BUDAYA ORGANISASI, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN PEMASARAN PT. NYONYA MENEER SEMARANG - Khairanda Satria; Handoyo Djoko Waluyo; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Human resources is one factor that strategic and fundamental in the organization. The role of human resources will determine the success or failure of the organization in achieving its vision and mission that has been set. In order to determine the extent to which the presence, role and contribution of human resources in achieving organizational success, of course necessary performance measurement. Employee performance marketing can be seen from the achievement of sales targets, but there are employees who have not been able to realize a given target. The aim of this study was to determine the effect of organizational culture, career development and compensation to employee performance marketing division of PT. Nyonya Meneer Semarang. This study uses census sampling sampling techniques against 38 employees of the marketing department of PT. Nyonya Meneer Semarang. Collecting data in this study using a questionnaire and interviews. The data obtained were analyzed qualitatively and quantitatively through validity and reliability test. While data analysis is done through a simple linear regression analysis, multiple linear regression, t-test and F test. The results of the study showed that there are significant positive and significant correlation between organizational culture, career development and compensation to employee performance marketing division of PT. Nyonya Meneer Semarang. Advice can be given is to further increase the focus on the variable compensation for the performance of employees is increasing.